METODE PEMBELAJARAN PENJASKES UNTUK SISWA TUNANETRA DI SLB BINA INSANI BANDAR LAMPUNG ( METODE TAKTIL ) - Najwa Inari, Ainun; Wicaksono , Lungit; Jaya Sumantri, Riyan; Siswoyo, Joan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the application of physical education teaching methods for visually impaired students at SLB Bina Insani Bandar Lampung (tactile method). The research method used in this study is descriptive qualitative, with data collection using observation, interviews, and documentation techniques. Data analysis was conducted using an interactive qualitative data analysis model with three stages, namely data reduction, data presentation, and conclusion drawing and verification. The results of the study show that 1) the application of the tactile method in physical education at SLB Bina Insani Bandar Lampung is carried out in accordance with the principles of adaptive learning for children with special needs (ABK), especially the visually impaired. 2) The obstacles encountered during physical education are the initial conditions of students who are not accustomed to doing sports activities. Therefore, adaptation is needed before they are able to follow the learning process using the tactile method. The challenge faced by physical education teachers is that the material must be conveyed concretely before students can practice the movements, because the information received by the visually impaired is abstract. 3) Physical education using the tactile method at SLB Bina Insani Bandar Lampung provides a good learning experience for visually impaired students. This helps students process movement information more concretely.